Multi-Area Optimal Power Flow Problem Through Parallel Processing - Do Carmo Yamaguti, Lucas [UNESP]; Home-Ortiz, Juan M. [UNESP]; Pourakbari-Kasmaei, Mahdi; Mantovani, Jose Roberto Sanches [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The conventional approach to managing the electrical power system (EPS) operation involves a single independent system operator solving the optimal power flow (OPF) problem. However, the reality is that the EPS comprises multiple areas controlled by independent system operators who must ensure the security and privacy of data in the energy market. This work introduces a mixed-integer nonlinear programming model for solving the multi-area OPF problem, enabling independent solution of each area in the EPS system via parallel processing. Validation of the proposed model and solution technique is conducted using the RTS-96 bus system, showcasing satisfactory solutions yielded by the multi-area approach. Additionally, the proposed model is extended and analyzed under a security-constrained approach by solving some contingencies in the system.
Keywords: Mixed-integer nonlinear programming; multi-area power systems; optimal power flow; parallel processing